Proses Produksi Dalam Pembuatan Konten Tutorial Make Up di TV9 Nusantara Surabaya - Anis Faul Lutfiana; Luthfi Hidayah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
This internship report discusses the production process in content creation at TV9 Nusantara Surabaya. The aim of this report is to provide a detailed overview of the stages involved in producing television programs, from planning and filming to content editing. The research methods used in this study were direct observation, interviews, and documentary analysis. The findings indicate that TV9 Nusantara Surabaya has a well-structured and organized production system. The production process starts with program planning, scriptwriting, equipment and material preparation, filming, and content editing. Challenges faced by the team include time constraints, limited human resources, and technological limitations. It is hoped that this report can provide a reference for similar institutions or other parties interested in